The Good Is Never Perfect: Why the Current Flaws of Voluntary Carbon Markets Are Services, Not Barriers to Successful Climate Change Action - Miltenberger, Oliver; Jospe, Christophe; Pittman, James (Frontiers in Climate, 2021)
The world’s current level of climate change action does not match its ambitions to tackle the issue, and its ambitions do not currently meet the levels of action science recommends. Voluntary carbon markets are one option proposed to lessen those disparities, and have been both criticized and championed by various groups. Critiques note them as being opaque, flawed, and ineffective. Yet they demonstrate tremendous potential for impact and unprecedented levels of finance. We contend that the critiques of these markets are not only resolvable, but are unavoidable challenges that must be addressed on the path to mobilizing climate change ambition and achieving targets. Furthermore, we believe that by 2050, the current discrete market-based solutions in climate action will become internalized aspects of our economies rather than separate remediations. This goal of internalizing the externalities that cause climate change will result in massive, sustained decarbonization, rapid reorganization of global economies, and an extraordinary push to invent, solve, and scale strategies that facilitate the transition. Pricing carbon is a key contemporary step for transitioning to that future. Voluntary carbon markets are one means to catalyze this action and while needing improvements, should be given appropriate leeway to improve and fulfil that role.